Quality of Life in medical residences in Mexico: A desperate cry (Revista de Medicina Clinica, 2019)
Education in medical residences is far from being a training that contemplates all the dimensions required by the student, they are also plagued by outdated methods and strategies that under a â€œhidden curriculumâ€, foster a misrepresented education, devoid of humanism and cordiality. The contrast overflows it in a world full of scientific and technological progress in its practice as a professional and a stagnation in the educational paradigms in its formation
Keywords: Keywords: Medical residences, quality of life, education